Islam, Muslims, and COVID-19 : The Intersection of Ethics, Health and Social Life in the Diaspora - Al-Deen, Aminah; Padela, Aasim I. (Muslim Minorities, 2024)
This volume brings together diverse disciplinary perspectives to provide a multidisciplinary and multidimensional account of Muslim ethics operating in the COVID-19 era, where scriptural values, lived experiences, societal structures, and cultural contexts combine in fresh and diverse ways. Indeed, Islamic ethical evaluation often ignores contributions from the social sciences, and contextual factors are not fully understood when issuing Islamic edicts. This volume thus aims at a more connected account of how religious concerns generated challenges and how Muslims lived out their religious values during the pandemic. Alongside descriptive accounts are normative evaluations, and insights from interviews are connected with survey analyses; in this way, the chapters render a more complete account of the intersectional engagement of Muslim healthcare professionals and community members living in minority contexts with the early stages of the COVID-19 pandemic.